The implementation of conflict of interest policies for Ministers in the EU Member States : More, stricter and institutionalized – but less effective? - Demmke, Christoph; Autioniemi, Jari; Lenner, Florian (Vaasan yliopisto, 2021)
All countries agree that Holders of Public Office are role models, should exercise ethical leadership and accept highest ethical requirements. If countries want these standards and requirements to be effective, they must invest in the institutionalisation, implementation, monitoring and enforcement of ethics policies. In the field of Conflicts of Interests (CoI), countries continue to introduce ever more and ever stricter standards and requirements. They also invest ever more resources in the institutionalization of CoI policies. Because of the sophisticated nature of these policies, the effective implementation remains a challenge. This article explains the lack of effectiveness, drawing on longitudinal insights derived from two studies conducted by the authors in 2007 and 2020. We rely on data generated in an expert survey with public officials from 18 EU Member States. Our results show that countries regulate ever more CoI issues, broaden CoI concepts and introduce tougher behavioural standards, shifting the focus towards an individualised “bad person” logic instead of systemic or institutional approaches. If CoI scandals emerge, the focus is almost always on individual misbehaviour. Although Member States invest more in the implementation of CoI policies, they shy away from enforcing policies and rules against ministers. As such, policies become more complex, the institutionalisation of CoI policies more professional (yet also more fragmented) and the management of CoI ever more resource intensive. Overall, formalism, administrative burdens and the politicization of CoI policies are increasing. As such, we conclude that CoI policies have not become more effective.
Keywords: European Union countries; ethics; international comparison; politics; conflict management; corruption; political decision making; public administration; fi=Julkisjohtaminen|en=Public Management|